A new crab of the genus Nanoplax from the Gulf of Mexico, and assignment of Micropanope pusilla to a new genus (Crustacea, Brachyura, Pseudorhombilidae) - Felder, Darryl L. (Zootaxa, 2020)
Nanoplax thomai n. sp. is described from the Gulf of Mexico, representing the second species of the genus. The description is based upon a number of specimens previously misidentified as Micropanope truncatifrons Rathbun, 1898, including one so represented in recent molecular phylogenetic analyses. As restricted, Micropanope truncatifrons remains known with certainty from only the limited type series, which does not include a mature male, and sequence quality tissues are not available for molecular phylogenetic analyses. Its generic placement remains questionable following morphological study of its type materials and comparisons to specimens representing other present and former members of Micropanope Stimpson, 1871. Those comparisons underscore that morphological and molecular distinctions warrant assignment of Micropanope pusilla A. Milne-Edwards, 1880 to a new genus, herein designated as Pseudopanopeus n. gen.